Immunogenicity of a killed bivalent (O1 and O139) whole cell oral cholera vaccine, Shanchol, in Haiti. - Richelle C Charles; Isabelle J Hilaire; Leslie M Mayo-Smith; Jessica E Teng; J Gregory Jerome; Molly F Franke; Amit Saha; Yanan Yu; Paul Kováč; Stephen B Calderwood; Edward T Ryan; Regina C LaRocque; et al. (PLoS Neglected Tropical Diseases)
Background Studies of the immunogenicity of the killed bivalent whole cell oral cholera vaccine, Shanchol, have been performed in historically cholera-endemic areas of Asia. There is a need to assess the immunogenicity of the vaccine in Haiti and other populations without historical exposure to Vibrio cholerae. Methodology/principal findings We measured immune responses after administration of Shanchol, in 25 adults, 51 older children (6-17 years), and 47 younger children (1-5 years) in Haiti, where cholera was introduced in 2010. A≥4-fold increase in vibriocidal antibody titer against V. cholerae O1 Ogawa was observed in 91% of adults, 74% of older children, and 73% of younger children after two doses of Shanchol; similar responses were observed against the Inaba serotype. A≥2-fold increase in serum O-antigen specific polysaccharide IgA antibody levels against V. cholerae O1 Ogawa was observed in 59% of adults, 45% of older children, and 61% of younger children; similar responses were observed against the Inaba serotype. We compared immune responses in Haitian individuals with age- and blood group-matched individuals from Bangladesh, a historically cholera-endemic area. The geometric mean vibriocidal titers after the first dose of vaccine were lower in Haitian than in Bangladeshi vaccinees. However, the mean vibriocidal titers did not differ between the two groups after the second dose of the vaccine. Conclusions/significance A killed bivalent whole cell oral cholera vaccine, Shanchol, is highly immunogenic in Haitian adults and children. A two-dose regimen may be important in Haiti, and other populations lacking previous repeated exposures to V. cholerae.